Розвиток психологічних задатків абітурієнта як передумова становлення висококваліфікованого фахівця - Білоус, Наталя Володимирівна; Белоус, Наталья Владимировна; Віlous, Natalia; Зайцева, Наталя Володимирівна; Зайцева, Наталья Владимировна; Zаitsеvа, Natalia (My University, 2007)
UK: Висвітлено результати соціологічного дослідження у ТДАТА відносно психологічних факторів вибору студентами професії, які можуть бути корисніша і для інших вузів АПК України. RU: Рассматриваются вопросы подготовки будущих кадров уже на этапе профессиональной ориентации и выбора учебного заведения с учетом социально-психологических задатков потенциального специалиста. Согласно результатам проведенного эмпирического исследования можно определить общие тенденции выбора профессии в соответствии с доминирующим у конкретной личности типом поведения и тем самым увеличить шансы абитуриента и студента на раскрытие и применение собственного профессионального потенциала. EN: This article deals with the problems of future specialists training in the phase of career guidance and choosing educational establishment considering potential employee’s social and psychological inclinations. According to the results of empirical research made it is possible to discover general profession choice trends corresponding to dominating behavior type of individual and increase university-entrant’s and student’s chances for showing and realization of own professional potential.
Развитие психологических задатков абитуриента как предпосылка становлення высококвалифицированного специалиста
Development of рsусlogісаl inclinations оf universitу applicants аs ргесоndition for a highly skilled sресіаlist forming
Keywords: освіта; абітурієнт; знання; професія